(untitled) (Journal of human and social sciences, 2026)
Higher education institutions aim to achieve excellence, effectiveness, and quality in their outputs through efficient management, integrity of staff, strong administrative structures, and continuous oversight. Governance has emerged as a modern concept crucial for universities worldwide, enabling them to prepare qualified human capital, address societal challenges, and contribute to comprehensive development across political, economic, social, technological, and security dimensions. Universities fulfill three main functions: teaching and training, conducting scientific research, and serving the community. Achieving these functions requires adopting effective governance frameworks to enhance institutional performance, output quality, and alignment with international standards. The study addresses the reality of governance implementation at Libyan universities, focusing on Ajdabiya University. It examines governance as a system of regulations, rules, and procedures designed to achieve high efficiency, accountability, transparency, and stakeholder participation. The research investigates the current state of governance practices in relation to laws, transparency, accountability, and participatory mechanisms, while identifying challenges and proposing recommendations to improve the performance of higher education institutions in Libya. The importance of this study lies in its focus on governance in Libyan higher education, providing practical insights into its application at Ajdabiya University and offering evidence-based suggestions for policymakers and university administrators to enhance institutional effectiveness and achieve strategic objectives.